Bārhika sammelana '79, Ḍhākā Sāṃbādika Iuniẏana, Ilā, 2rā, o 3rā Eprila, Jātiẏa Presa Klāba (Ḍiiuje, 1979)
Souvenir issued on the occasion of the annual conference of the Dacca Union of Journalists; comprises articles on freedom of the press, press and politics, freedom of expression, etc.